2017
DOI: 10.1093/bja/aew401
|View full text |Cite
|
Sign up to set email alerts
|

Transnasal humidified rapid-insufflation ventilatory exchange (THRIVE) in children: a randomized controlled trial

Abstract: ACTRN12615001319561.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
172
2
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(192 citation statements)
references
References 25 publications
(29 reference statements)
11
172
2
3
Order By: Relevance
“…Therefore, a weight‐adjusted THRIVE technique (Table ) has been evaluated in a randomized controlled trial in well children with normal airways and cardiorespiratory function comparing its efficacy and safety as an apnoeic oxygenation adjunct. The expected desaturation time for a child is determined by functional residual capacity which is age dependent, and therefore, this study examined four different age groups in the range from 0 to 10 years and found the same trend among all four groups . This study has also demonstrated an extended safe apnea time of at least twice the age‐expected time but failed to show any ventilatory carbon dioxide exchange during the apnea with both groups having a rate of rise of carbon dioxide of 2.4 mm Hg/min.…”
Section: Physiology Of Apnoeic Oxygenationmentioning
confidence: 68%
“…Therefore, a weight‐adjusted THRIVE technique (Table ) has been evaluated in a randomized controlled trial in well children with normal airways and cardiorespiratory function comparing its efficacy and safety as an apnoeic oxygenation adjunct. The expected desaturation time for a child is determined by functional residual capacity which is age dependent, and therefore, this study examined four different age groups in the range from 0 to 10 years and found the same trend among all four groups . This study has also demonstrated an extended safe apnea time of at least twice the age‐expected time but failed to show any ventilatory carbon dioxide exchange during the apnea with both groups having a rate of rise of carbon dioxide of 2.4 mm Hg/min.…”
Section: Physiology Of Apnoeic Oxygenationmentioning
confidence: 68%
“…A new technique called Transnasal Humidified Rapid‐Insufflation Ventilatory Exchange utilises nHF to prolong the safe apnoeic time following induction of anaesthesia, likely due to upper airway splinting, continuous insufflation and dead space washout . This technique has recently been evaluated in healthy children undergoing anaesthesia and was found to significantly prolong the time to desaturation. No studies have investigated this technique in preterm infants who frequently become unstable during intubation.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Julia advocated for a conceptual shift in our approach, in which ‘every emergent airway is considered a potentially difficult airway’. She discussed methods to maximise the time from apnoea to critical desaturation including methods of maximising pre‐oxygenation, apnoeic oxygenation techniques (including trans‐nasal humidified high‐flow oxygen) and re‐oxygenation. Julia likened emergency intubation to a ‘flash mob’ setup for a common task, and discussed the advantages of adopting cognitive offloading techniques such as standardised equipment, a standardised approach (common airway algorithm) and using checklists.…”
Section: Communication Tips and Trapsmentioning
confidence: 99%